Reliability of resting intramuscular fiber conduction velocity evaluation. - Methenitis, S; Karandreas, N.; Terzis, G. (Scand J Med Sci Sports, 2018)
Characterization of the least number of muscle fibers analyzed for a quick and reliable, evaluation of intramuscular fiber conduction velocity (MFCV) is of importance for sport scientists. The aim of this study was to evaluate the reliability of vastus lateralis' intramuscular MFCV measuring either 25 or 50 different muscle fibers per participant, as well as to compare intramuscular MFCV measured in 25 (C ), 50 (C ), or 140 (C ) muscle fibers. Resting vastus lateralis' MFCV was measured in 21 young healthy males (age 22.1±2.4 years) using intramuscular microelectrodes in different days. Test-retest reliability of MFCV's parameters was calculated for C and C , while MFCV was compared among C , C , and C . Significant differences of MFCV parameters were observed between C condition and those of C and C . The differences in MFCV values between conditions C and C were non-significant. A close correlation was found for MFCV between C and C (r=0.884-0.988, P=.000). All reliability measures of MFCV measured with 50 fibers were high (eg, ICC=0.813-0.980, P=.000), in contrast to C (eg, ICC=0.023-0.580 P>.05). In conclusion, an average of 50 different fibers per subject is sufficient to provide a quick and reliable intramuscular evaluation of vastus lateralis MFCV.
Keywords: Adult; Electromyography; Humans; Male; Muscle Fibers, Skeletal; Quadriceps Muscle; Reproducibility of Results; Rest; Young Adult